Microarchitecture of Heterotopic Ossification in Fibrodysplasia Ossificans Progressiva: An HR-pQCT Case Series - Botman, Esmée; Bevers, Melissa S. A. M.; Wyers, Caroline E.; van Rietbergen, Bert; Teunissen, Bernd P.; Raijmakers, Pieter G.; Netelenbos, Jan Coen; van den Bergh, Joop P.; Eekhoff, Elisabeth M. W. (Frontiers in Cell and Developmental Biology, 2021)
It is challenging to study heterotopic ossification (HO) in patients with fibrodysplasia ossificans progressiva (FOP) due to the contraindication of invasive techniques (i.e. bone biopsies), which can trigger flare-ups. The aim of this case study was to assess mature HO at microarchitectural level non-invasively with high-resolution peripheral quantitative computed tomography (HR-pQCT). Depending on the patient’s mobility, HR-pQCT scans were acquired of peripherally-located HO and standard distal radius and tibia regions in two FOP-patients, a 33-year-old woman and a 23-year-old man, with the classical mutation (p.R206H). HO was located around the halluces, ankles and in the Achilles tendon. Standard HR-pQCT analyses were performed of the distal radius, tibia, and HO to quantify bone mineral density (BMD) and bone microarchitecture. Micro-finite element analysis was used to estimate failure load (FL). The outcomes were compared between HO and neighboring skeletal bone and with an age- and gender-matched normative dataset from literature. Bone parameters of the radius were within the interquartile range (IQR) of normative data. In contrast, in the tibiae of both patients, total and trabecular BMD were below the IQR, as were trabecular bone volume fraction, number, and thickness, cortical thickness, and FL. Trabecular separation and heterogeneity were above the IQR. Isolated HO in the Achilles tendon had a lower total, trabecular, and cortical BMD, trabecular bone volume fraction, and cortical thickness than the normative tibia data. Trabecular microarchitecture was within the IQR, and FL was approximately 10 times higher than of the neighboring tibia after accounting for areal differences. Other scanned HO could only be qualitatively assessed, which revealed coalescence with the neighboring skeletal bone, development of a neo-cortex, and partial replacement of the original skeletal cortex with trabeculae. To conclude, isolated HO seemed microarchitecturally more comparable to reference tibia data than the peripheral skeleton of the FOP-patients. Also, HO and skeleton appear to be able to become one entity when contiguous.